Second-look arthroscopic findings and clinical outcomes after management of intra-articular lesions in acute ankle fractures with arthroscopy. Issue 7 (October 2021) - Kim, Jung-Han; Gwak, Heui-Chul; Park, Dae-Hyun; Lee, Chang-Rack; Jung, Soo-Hwan; Kim, Jeon-Gyo; Lee, Sun Joo
Highlights: Ankle fractures do not always show favorable clinical progress after anatomical reduction and stable fixation. Intra-articular lesions may affect the clinical outcome of ankle fracture. Pain after the treatment of ankle fracture was associated with the number of osteochondral lesions. Abstract: Background: Anatomically surgical reduction of ankle fractures does not always result in a clinically favorable outcome. Arthroscopic examination combined with treatment of intra-articular lesion may related to clinical outcomes Objectives: The purpose of the present study was to review initial and second look arthroscopic finding of acute ankle fracture and to evaluate clinical outcomes. Results: Lauge-Hansen classification system of ankle fractures included supination-external rotation type (n = 24), supination-adduction type (n = 3), pronation-external rotation type (n = 7), and pronation-abduction type (n = 6), total 40 ankles. Osteochondral lesions were found in 25 ankles (62%) with an initial arthroscopic finding of acute ankle fracture. Newly discovered chondral lesions in secondary arthroscopy were found in 17 cases. According to the Ferkel and Cheng staging at secondary arthroscopy, 4 of 25 ankles with osteochondral lesions of the talus were deteriorating (more than stage D). In terms of ICRS overall repair grades, 5 ankles (20%) were abnormal (grade III). Diffuse synovitis and arthrofibrosis were found in 12 and 7 ankles, respectively, in secondary arthroscopy, and correlations were found between AOFAS scores, VAS and intra-articular lesions. Conclusion: Second-look arthroscopic examination combined with treatment of intra-articular lesion such as arthrofibrosis and osteochondral lesion arising from ankle fracture surgery may consider to improve clinical outcomes.